The Housing Bubble in the Spanish Press (2003-2013). An analysis of the opinions of political and expert sources - Arrese, Ángel (2018)
This study compiles and analyzes data on views of politicians and economists reported in news articles published in five Spanish dailies (the three leading national newspapers –El País, El Mundo and ABC-, and the two leading financial newspapers –Expansión and Cinco Días-). Quantitative content analysis will be used as the basic methodology for research. This content analysis will be focused on the coincidences and divergences between the nature, structure and frames of the opinions and comments on the bubble made by these policy makers and experts in two different periods, before and after the bubble burst. The general hypothesis of the research is that before the crisis –especially among politicians- there was not a real discussion on the threat of a housing bubble, its causes and probable consequences, but a quite orchestrated “negationist” consensus.